ÁDEBIYATTI OQITIWDA INFORMACION TEXNOLOGIYALARDAN PAYDALANIW MÁSELELERI - Kazaxbaev, S. (SCIENCE and SOCIETY, 2022)
The article analyzes the need for teachers to effectively use modern computer technologies and know the available technical tools.
Keywords: computer; information; communication; presentation; information technology